Compared with saturated fatty acids, dietary monounsaturated fatty acids and carbohydrates increase atherosclerosis and VLDL cholesterol levels in LDL receptor-deficient, but not apolipoprotein E-deficient, mice - Merkel, Martin (The National Academy of Sciences, 2001)
Heart-healthy dietary recommendations include decreasing the intake of saturated fatty acids (SFA). However, the relative benefit of replacing SFA with monounsaturated fatty acids (MUFA), polyunsaturated fatty acids (PUFA), or carbohydrates (CARB) is still being debated. We have used two mouse models of atherosclerosis, low density lipoprotein receptor-deficient (LDLRKO) and apolipoprotein E-deficient (apoEKO) mice to measure the effects of four isocaloric diets enriched with either SFA, MUFA, PUFA, or CARB on atherosclerotic lesion area and lipoprotein levels. In LDLRKO mice, compared with the SFA diet, the MUFA and CARB diets significantly increased atherosclerosis in both sexes, but the PUFA diet had no effect. The MUFA and CARB diets also increased very low density lipoprotein-cholesterol (VLDL-C) and LDL-cholesterol (LDL-C) in males and VLDL-C levels in females. Analysis of data from LDLRKO mice on all diets showed that atherosclerotic lesion area correlated positively with VLDL-C levels (males: r = 0.47, P < 0.005; females: r = 0.52, P < 0.001). In contrast, in apoEKO mice there were no significant dietary effects on atherosclerosis in either sex. Compared with the SFA diet, the CARB diet significantly decreased VLDL-C in males and the MUFA, PUFA, and CARB diets decreased VLDL-C and the CARB diet decreased LDL-C in females. In summary, in LDLRKO mice the replacement of dietary SFA by either MUFA or CARB causes a proportionate increase in both atherosclerotic lesion area and VLDL-C. There were no significant dietary effects on atherosclerotic lesion area in apoEKO mice. These results are surprising and suggest that, depending on the underlying genotype, dietary MUFA and CARB can actually increase atherosclerosis susceptibility, probably by raising VLDL-C levels through a non-LDL receptor, apoE-dependent pathway.